Word characteristics and speech production accuracy in children with auditory brainstem implants: a longitudinal triple case report. (2nd September 2021) - Faes, Jolien; Gillis, Steven
ABSTRACT: Auditory brainstem implants (ABI) in children in the first years of life is a recent innovation. Analyses of their speech and language development on the basis of spontaneous language samples are still largely lacking. The aim was to investigate the phonological complexity of the words children with ABI use in their spontaneous speech, and to compare their accuracy with that of children with cochlear implants (CI) and children with normal hearing (NH). Longitudinal recordings of spontaneous speech were collected of three children with ABI. Children with ABI target mainly words of low phonological complexity in their spontaneous speech, just as children with NH and children with CI do. The complexity of the words they attempt increases over time, but this development is less outspoken in comparison to children with CI and NH at the same hearing ages. The accuracy of the ABI children's word productions is situated in the lower ranges of the 95% confidence intervals of the NH and the CI groups, and – depending on the specific measure – even fall below the 95% border. The ABI intervention appears to be beneficial in the three cases studied, although their development is slow compared to children with CI and NH.